Health Literacy and Clear Bedside Communication: A Curricular Intervention for Internal Medicine Physicians and Medicine Nurses - Jill Allenbaugh; Carla L. Spagnoletti; Laurie Rack; Doris Rubio; Jennifer Corbelli (Association of American Medical Colleges, 2019)
Introduction Communication remains the backbone of patient-provider relationships, and many health outcomes have been directly attributed to both effective and ineffective communication. We developed an educational intervention to improve bedside communication and increase use of health literacy principles, in part as a response to suboptimal inpatient satisfaction scores. Methods Our intervention consisted of a beside communication curriculum among 37 attending medicine physicians, 76 internal medicine residents, and 85 bedside nurses. The 1- to 1.5-hour curriculum included a didactic session to teach health literacy principles, video demonstrations, group discussion, and role-play. Attending physicians' health literacy knowledge, attitudes, and confidence were evaluated using pre- and postsurveys. Evaluation of the curriculum included Likert-type questions and free-text responses. Results Attending physicians' knowledge and confidence improved (74% correct pre, 100% correct post, p < .001; 4.41 pre, 4.68 post, p = .002, respectively). Certain attitude domains also improved, including importance of team introductions and nurse contributions to bedside rounds (p < .001). Both residents and nurses found the curriculum valuable and planned to incorporate it into their bedside rounding. Discussion A brief, low-cost curricular intervention focusing on clear communication skills and health literacy principles resulted in significant improvements in knowledge and attitudes of attending physicians and was readily incorporated by resident physicians and nurses. This curriculum can be easily implemented in a variety of settings to improve bedside patient-physician communication.